Insulin-like growth factor (IGF)-I, IGF-binding protein (IGFBP)-1, and fibroblast growth factor (FGF) 21 serum levels in Chinese women with and without gestational diabetes. Issue 5 (2017) - Seto-Young, Donna; Avtanski, Dimiter; So-Young, Kim; Sy, Vanessa; Liao, Emilia; Liu, George; Wan, Stephen; Lesser, Martin; Poretsky, Leonid
No abstract available